2021
DOI: 10.1177/14624745211007192
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of normality: Finnish prisoners envisioning their future

Abstract: The ambition of living ‘a normal life’ appears to be common among prisoners prior to release. Besides portraying for the life desired upon release, the notion of a normal life can say something about what the persons aspiring to it thinks of their present life, what they want their life to be like in future, and what they consider attainable. This article explores the subjective and social considerations of prisoners’ desires for normality. Qualitative interviews with prisoners at low-security open prisons in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Visions of future personhood often evolved into considerations of how the interviewees’ life interconnected with those of others relationally. Similar to Seed's analysis of long-term imprisonment, I found that this imaginative and ‘narrative labour’ (Warr, 2020) was ‘not a reaffirmation of who one was , or a doubling down on beliefs one held before entering prison, but a reassessment of who one will be going forward’ (Seeds, 2021: 13, emphases in original). Hjalmar, for example, longed to be a person his family would ‘miss’ when he died (Hjalmar, EE1, Norway).…”
Section: Radical Hopementioning
confidence: 64%
See 1 more Smart Citation
“…Visions of future personhood often evolved into considerations of how the interviewees’ life interconnected with those of others relationally. Similar to Seed's analysis of long-term imprisonment, I found that this imaginative and ‘narrative labour’ (Warr, 2020) was ‘not a reaffirmation of who one was , or a doubling down on beliefs one held before entering prison, but a reassessment of who one will be going forward’ (Seeds, 2021: 13, emphases in original). Hjalmar, for example, longed to be a person his family would ‘miss’ when he died (Hjalmar, EE1, Norway).…”
Section: Radical Hopementioning
confidence: 64%
“…Hope has the capacity to animate a person's 'moral ambitions to do better and be better; it orients and shapes [his or her] autonomy' (Brownlee, 2021: 597). We know that most people who have committed an offence hope and yearn to 'make good' (Maruna, 2001), lead conventional lives and that almost everyone stops offending eventually (Halsey et al, 2017;Harris, 2011;McNeill, 2018;Nugent and Schinkel, 2016;Shapland and Bottoms, 2011;Villman, 2021). However, the sociology of imprisonment recognizes both the potential benefits and tragedy of hoping.…”
Section: The Nature Of Hopementioning
confidence: 99%
“…Imprisonment had either disrupted or damaged citizenship for many participants, with some feeling their potential citizenship had received such irreparable damage it had been entirely lost, making an imagined future citizen self no longer attainable. Just as imprisonment ‘disrupted their normal life’ (Villman, 2021: 8), for some, imprisonment had also disrupted their prior engagement as ‘active citizens’ outside which they hoped, albeit with apprehension about the hurdles involved, to return to. Several participants described how they had been involved in what they saw as positive and meaningful citizenship before incarceration, whether through paid employment, running businesses, or voluntary contributions to local communities.…”
Section: The Prison's ‘Shadow’ Over Meaningful Future Citizenshipmentioning
confidence: 99%
“…The desire to live a ‘normal’ life is prevalent in prisoners’ narratives about their post-release futures. Many aspire to the humble stability of a crime-free existence and conventional work and home life, their imprisonment being perceived as in opposition to such ‘normalcy’ (Villman, 2021). In this study, narratives of ‘normal life’ and citizenship were intimately connected, with participants frequently understanding citizenship as synonymous with normality.…”
Section: Returning Citizens: Aspirations Of ‘Normal’ or ‘Active’ Citi...mentioning
confidence: 99%
See 1 more Smart Citation